Faktor Yang Berhubungan Dengan Praktik Safety Driving Pada Pengemudi Angkutan Kota Jurusan Banyumanik-Johar Kota Semarang - Nurcahyo Adinugroho; Bina Kurniawan; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Safety driving is a driving behavior to help driver in avoiding traffic problems. Data from the Directorate General of Land Transportation or “Direktorat Jenderal Perhubungan Darat” shows, the number of public transport cars in the year 2012 was 10 million units, an increase of 1.2 million units from the previous year. The purpose of this study was to analyze the factors related to safety driving practice of public transport driver of Banyumanik-Johar route in Semarang. This research used quantitative research that employed cross sectional study. This research utilized purposive sample approach. The population in this study was the drivers of public transport of Banyumanik-Johar route. The total number of drivers was 204 people. Thus, a total sample of 40 respondents were selected based on age criteria that was between 18 to 40 years old. Rank Spearman test was used at a significance level of 5%. The results showed that education was not significanly associated with safety driving with p-value = 0,763. Work period was not significanly associated with safety driving with p-value = 0,471. Knowledge was significanly associated with safety driving with p-value = 0,004. The supervisor role was not significanly associated with safety driving with p-value = 1. The friends role was not significanly associated with safety driving with p-value = 0,616. The car condition was not significanly associated with safety driving with p-value = 0,108